The spoilage yeast Zygosaccharomyces bailii forms mitotic spores : a screening method for haploidization - Rodrigues, Fernando José dos Santos (2003)
Zygosaccharomyces bailii ISA 1307 and the type strain of this spoilage yeast show a diploid DNA content. Together with a rather peculiar life cycle in which mitotic but no meiotic spores appear to be formed, the diploid DNA content explains the observed difficulties in obtaining auxotrophic mutants. Mitotic chromosome loss induced by benomyl and selection on canavanine media resulted in three haploid strains of Z. bailii. This new set of Z. bailii strains allows the easy isolation of recessive mutants and is suitable for further molecular genetic studies.